Properties of Calcined Oebelo Red Soil Modified Fly Ash based Geopolymer - Andrie Harmaji; Partogi Hasudungan Simatupang; Ruslan Ramang; Ari Esclesias Sinaga (Jurnal Rekayasa Sipil, 2022)
Research on fly ash has developed rapidly in recent years, one of which is its use as an environmentally friendly geopolymer concrete material. This research study the effect of calcination temperature and duration of red soil to compressive strength and setting time of fly ash based geopolymer paste. The red soil calcination process was carried out with variations in temperature of 400°C, 600°C, and 800°C for 4 and 8 hours of calcination. The activator solution was prepared by mixing a solution of NaOH with a solution of Na2SiO3 with a 1:1 composition. Sample treatment was carried out in 2 types, with ambient curing type and dry curing type. From the results of this study, the fastest setting time and maximum compressive strength of geopolymer paste of 23.14 MPa achieved at 800°C red soil calcination at 8 hours, and dry curing.